Argentina Between the Great Powers, 1939-46 - Di Tella, Guido. author. aut Link
XIV, 212 p.
Keywords: An examination of Argentina's international behaviour during World War II. Relationships with the UK, the USA and Germany are considered, and in particular, the USA's long term hostile attitude towards the only country in Latin America that tried to question the American hegemony over the region.